SET OF WELL LOCATION DETERMINATION, DRILLING, COMPLETION, AND PRODUCTION METHODS IN RE-DEVELOPMENT OF A MATURE FIELD - Hari Karyadi Oetomo (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2018)
XYZ oil field has been on production for 30 years, and has produced 189 MMBO of oil out of 491 MMBO of Original Oil in Place.  The reservoir consists of reefal limestone carbonate rock.  Initially, oil production was mainly coming from reservoir fracture; while rock matrix acted as secondary porosity.  The field is the largest field in the area, with 40% of recovery factor.  This number is high, but comparing to other fields with the same reservoir flow characteristics in the adjacent area, this number is the lowest.  By increasing recovery factor of 0.5%, it will add 2 MBO of oil reserves, which is still feasible to be further re-developed.  Several last well being drilled were using spesifics methods which are different from previous wells' methods; and the results were successful.  The methods are conventional method which included well location determination by using engineering maps, drilling technique, completion technique and production methods.  The preliminary result of the field re-development yield to 40% water cut wells in the area with wells of 98% water cut.